Invisible Voids: The Zero Consumption Real Estate Vacancy Identification Method - Souza-Mc Murtrie, Ada Abrantes Penna (Revista Brasileira de Gestão Urbana, 2025)
As urbanisation in Brazil has escalated, so has the issue of real estate vacancy, with the number of empty houses now surpassing the housing deficit. Despite widespread criticism of this situation, information about these vacant properties remains unknown, mainly due to a scarcity of data. This study presents the Zero Consumption Real Estate Vacancy Identification Method (ZCREVIM), which utilises georeferenced electricity usage data from Belo Horizonte, Brazil. The method identifies potentially vacant properties using two spatial analysis models that process data through both absolute and relative numbers. I tested the method on a municipal scale in Belo Horizonte and on a local scale in the Centro neighbourhood. I discuss a limitation observed from the municipal scale results: it cannot be applied in areas with a significant number of illegal connections to the electricity network. From the Centro results, I thoroughly investigated 67 areas of interest to verify real estate vacancy through Google Street View, uncovering 16 demonstrably vacant buildings and 23 with solid evidence of unoccupancy. ZCREVIM provides public authorities with a tool to monitor real estate vacancy, aiding in the spatiotemporal identification of this phenomenon at the most granular urban scale: the property.